Efficacy of intraoperative subanaesthetic dose of ketamine on post-operative analgesia for patients undergoing single level lumbar discectomy under general anesthesia: A placebo control randomized clinical study - Sowmya Madihalli Janardhan Iyengar,; Shankar Kantharaju,; Shubha Mysore Ramesh, (Asian Journal of Medical Sciences, 2023)
Background: Sub-anesthetic ketamine is becoming increasingly popular for opioid sparing analgesic properties. Aims and Objectives: This study was done to determine the efficacy of intraoperative infusion of sub-anesthetic dose of ketamine on post-operative analgesia in single level lumbar discectomy surgeries. Materials and Methods: A prospective, randomized, and control study was carried on 60 patients of American Society of Anesthesiologists I and II aged between 18 and 65 years undergoing single level lumbar discectomy under general anesthesia. After induction of anesthesia, Group A received Ketamine 0.3 mg/kg intravenous (IV) bolus followed by infusion at 4 μg/kg/min and Group B received 0.9% saline bolus dose of similar volume and infusion was started at similar rate. Post-operative pain relief, opioid sparing effect, and side effects if any were recorded. Results: There was significant difference (P<0.001) in post-operative Numeric Rating scores for initial 6 h in Group A patients compared to Group B and prolonged duration of analgesia (8.5 vs. 4.25 h) along with reduced postoperative tramadol consumption. Conclusion: In lumbar spine discectomy, intraoperative ketamine infusion at sub-anesthetic doses produces more effective post-operative analgesia along with opioid sparing effect without any side effects.